Proceedings of the 3nd ACM Workshop on Performance Monitoring and Measurement of Heterogeneous Wireless and Wired Networks 2008
DOI: 10.1145/1454630.1454639
|View full text |Cite
|
Sign up to set email alerts
|

Performance of wireless network simulators

Abstract: Designing protocols for wireless networks is a challenging task. Combined with the fact that such networks are often deployed for critical missions like forest fire detection in the WSN scenario or have to function properly and efficiently for an extended period of time, it is desirable to thoroughly test, analyze and evaluate newly developed communication protocols before deployment. In order to do this, simulations are a good compromise between cost/complexity and accuracy of the results. Since there are man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Specifying the outstanding aspects of each simulator and making use of it in simulator selection was the aim and the foremost problems in MANET simulators were summarized [10]. With a simple topology control algorithm, Orfanus et al made a comparison of wireless network simulators [11]. In a comprehensive technical report prepared by Begg et al, it was indicated that discrete event simulation would be an important method in service availability and flexibility studies in next-generation network simulators [8].…”
Section: Related Workmentioning
confidence: 99%
“…Specifying the outstanding aspects of each simulator and making use of it in simulator selection was the aim and the foremost problems in MANET simulators were summarized [10]. With a simple topology control algorithm, Orfanus et al made a comparison of wireless network simulators [11]. In a comprehensive technical report prepared by Begg et al, it was indicated that discrete event simulation would be an important method in service availability and flexibility studies in next-generation network simulators [8].…”
Section: Related Workmentioning
confidence: 99%
“…In most cases, a simulation trace file is created, and is used to plot graph and/or to create animation. NS2 consists of two key languages: C++ and Object-oriented Tool Command Language (OTcl) [7,8]. While the C++ defines the internal mechanism (i.e.…”
Section: Ns -2mentioning
confidence: 99%
“…This simulation software itself should be modular, customizable and should allow embedding simulations into larger network applications. An OMNET++ model consists of modules that communicate with message passing [8]. The active modules are termed simple modules, they are written in C++, using the simulation class library.…”
Section: Figure 6: Overview Of Basic Modules In Omnet++mentioning
confidence: 99%
See 1 more Smart Citation
“…The paper compares the amount of effort needed for installation, familiarization, implementation (number of lines of code and number of lines for configuration needed to achieve a specific goal), and interpretation of the collected statistics. Reference [5] is a revised version of [4] made by the same authors, and reports a similar, but updated study with the same network simulators (J-Sim, OMNet++, ns-2, and ShoX). All these previous works are different from ours since the authors do not focus on VANET, and do not make any types of performance evaluation.…”
Section: Related Workmentioning
confidence: 99%